New distributional record of two species for the flora of Assam, India - Mipun, Puranjoy; Narah, Deiji; Kutum, Bob Christie; Sarma, Jintu (Plant Science Today, 2022)
Peliosanthes bipiniana D. K. Roy, N. Odyuo & N.Tanaka (Asparagaceae), an endemic plant and Begonia limprichtii Irmsch. (Begoniaceae) are recorded herewith as new distributional record for the flora of Assam. Morphological descriptions, phenology, taxonomic notes and field photos along with distribution map are provided for easy identification in the field.